Developing of the thermal calculation of the gasodiesel engine with internal formation of the mix air gas and validation by the experimentation - Maza Rubina, Arturo (2006)
The present work treats, on the performance of a mathematical model of simulation of the different processes that take place in the motors, which allow to establish the foreseeable indices of the operation of a motor of internal combustion of type gasodiesel, the methods of simulation of the operational cycle used in this work have been taken from recognized authors Soviet. This I calculate thermal fundamental has been made having in account that the combustible mixture this composing of GLP D2 in proportions of 40% and 60% respectively, whereas the GLP this compound of 50% of propano and 50% of Butane, to obtain the operation characteristics, has been developed a computacional program denominated Ajesa2004. The method of GLP provision is through the line of high pressure, which is made due to the hydrodynamic phenomena type water hammer which they are originated in this line, when the propelling valve, during the unloading of the provision of fuel when falling in its seat due to its belt of unloading forms a rarefaction wave; this wave makes open the valve of denominated retention RND. We made the grafico comparative analysis for which the obtained experimental values in the proving stand have been taken Newage, mounted with a diesel engine supercharged Perkins, such which they are necessary to optimize the indicated diagram and the characteristics of load and speed, obtained by means of a computacional program, table 1 and 2.